Thyroid gland metastasis arising from breast cancer: A case report - YANG, MEI (D.A. Spandidos, 2013)
The thyroid gland is an uncommon site for metastasis to develop and thus metastases arising from breast cancer are rarely observed. In the present study, we describe a case of a 45-year-old female with a three-year history of breast cancer who presented with a thyroid mass that was diagnosed as metastatic breast carcinoma by histopathological analysis of the subtotal thyroidectomy specimen. To ascertain the diagnosis of metastatic breast cancer, we evaluated two types of markers; those that possessed a similar expression status in the original and metastatic lesions [ER, PR and CerbB-2 (HER2/neu)], and those that are capable of differentiating between metastatic lesions and the surrounding thyroid components (TG and TTF-1). The results showed that ER, PR and CerbB-2 demonstrated a similar expression pattern in primary breast carcinoma and thyroid lesions. Meanwhile, in the thyroid lesions, the malignant cells showed negative staining for TG and TTF-1, which confirmed that lesions were not thyroid in origin. This case may prompt clinicians that although thyroid gland are uncommon metastatic site, a diagnosis of metastatic disease should be considered when new aggregates are identified in the thyroid glands and histopathological analysis may aid the diagnosis.